Molecular targets of endothelial phosphatidic acid regulating major depressive disorder. Issue 4 (24th October 2022) - Edwards, Michael J.; Wilson, Gregory C.; Keitsch, Simone; Soddemann, Matthias; Wilker, Barbara; Müller, Christian P.; Kornhuber, Johannes; Gulbins, Erich
Abstract: Major depressive disorder (MDD) is a severe disease of unknown pathogenesis with a lifetime prevalence of 10%. Therapy requires prolonged treatment that often fails. We have previously demonstrated that ceramide levels in the blood plasma of patients and in mice with experimental MDD are increased. Neutralization of blood plasma ceramide prevented experimental MDD in mice. Mechanistically, we demonstrated that blood plasma ceramide accumulated in endothelial cells of the hippocampus, inhibited phospholipase D (PLD) and thereby decreased phosphatidic acid in the hippocampus. Here, we demonstrate that phosphatidic acid binds to and controls the activity of phosphotyrosine phosphatase (PTP1B) in the hippocampus and thus determines tyrosine phosphorylation of a variety of cellular proteins including TrkB. Injection of PLD, phosphatidic acid, or inhibition of PTP1B abrogated MDD and normalized cellular tyrosine phosphorylation, including phosphorylation of TrkB and neurogenesis in the hippocampus. Most importantly, these treatments also rapidly normalized behavior of mice with experimental MDD. Since phosphatidic acid binds to and inhibits PTP1B, the lack of phosphatidic acid results in increased activity of PTP1B and thereby in reduced tyrosine phosphorylation of TrkB and other cellular proteins. Thus, our data indicate a novel pathogenetic mechanism of and a rapidly acting targeted treatment for MDD. Abstract : Major depressive disorder (MDD) is a severe and common chronic disease. We proposed that at least some forms of stress MDD induce an increase in the sphingolipid ceramide in the blood plasma. Here, we aimed to identify targets of blood plasma ceramide: Ceramide inhibits phospholipase D in endothelial cells thereby reducing phosphatidic acid in the hippocampus. The lack of phosphatidic acid results in increased activity of protein tyrosine phosphatase 1B, which dephosphorylates and inactivates the growth factor TrkB, a protein well‐known to be critical in the pathogenesis of MDD. The data indicate a novel pathogenetic mechanism for MDD.